THE EFFECTIVENESS OF VIRTUAL REALITY IN VOCATIONAL EDUCATION FOR FASHION DESIGN AND PRODUCTION - Irmayanti Irmayanti; Syahroni Hidayat; Heri Tri Luqman Budisantoso; Ahmad Mustamil Khoiron; Taofan Ali Achmadi (Universitas Labuhanbatu, 2026)
Purpose – The fashion industry must master the practical skills needed today to employ immersive technology like VR in Vocational Education and Training. Due to the cost and hazard of hands-on instruction, Indonesian vocational high schools have a skill gap. In order to deal with this problem, this study talks about the real-life outcomes of